2021
DOI: 10.3390/microorganisms9020362
|View full text |Cite
|
Sign up to set email alerts
|

How the Soil Microbial Communities and Activities Respond to Long-Term Heavy Metal Contamination in Electroplating Contaminated Site

Abstract: The effects of long-term heavy metal contamination on the soil biological processes and soil microbial communities were investigated in a typical electroplating site in Zhangjiakou, China. It was found that the soil of the electroplating plant at Zhangjiakou were heavily polluted by Cr, Cr (VI), Ni, Cu, and Zn, with concentrations ranged from 112.8 to 9727.2, 0 to 1083.3, 15.6 to 58.4, 10.8 to 510.0 and 69.6 to 631.6 mg/kg, respectively. Soil urease and phosphatase activities were significantly inhibited by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 63 publications
(78 reference statements)
0
5
0
1
Order By: Relevance
“…Oral intake of copper may cause hepatic and kidney disease, including Wilson's disease, related to copper accumulation in organs instead of being excreted by bile [63]. In addition to the harmful effects of these PTMs on human health, there are strong evidences that events of soil contamination by these three MTPs are related to disturbances of the soil ecosystem, which is related to deterioration of soil quality [64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Oral intake of copper may cause hepatic and kidney disease, including Wilson's disease, related to copper accumulation in organs instead of being excreted by bile [63]. In addition to the harmful effects of these PTMs on human health, there are strong evidences that events of soil contamination by these three MTPs are related to disturbances of the soil ecosystem, which is related to deterioration of soil quality [64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggested that soil pH was negatively correlated with groundwater depth. A previous study demonstrated that Sphingomonadaceae was able to secrete dehydrogenase to balance soil pH ( Gong et al, 2021 ). Increasing groundwater depth improve the relative abundance of Mortierellaceae in fungal community.…”
Section: Discussionmentioning
confidence: 99%
“…Soil enzymes play a significantly important role in various biochemical processes, particularly in the material cycle and in energy conversion in soil [ 38 , 43 ]. They are rather sensitive to heavy metals, and they are important indicators for evaluating soil contamination [ 44 , 45 , 46 ]. Urease, widely found in microorganisms and plants, is an essential enzyme in soils that can catalyze the hydrolysis of urea and increase the nitrogen contents in soils [ 38 , 47 ].…”
Section: Discussionmentioning
confidence: 99%